Sustaining Executive Functions During Sleep Deprivation: A Comparison of Caffeine, Dextroamphetamine, and Modafinil - Killgore, William D. S.; Kahn-Greene, Ellen T.; Grugle, Nancy L.; Killgore, Desiree B.; Balkin, Thomas J. (Sleep (New York, N.Y.), 2009)
Stimulant medications appear effective at restoring simple alertness and psychomotor vigilance in sleep deprived individuals, but it is not clear whether these medications are effective at restoring higher order complex cognitive capacities such as planning, sequencing, and decision making. After 44 hours awake, participants received a double-blind dose of one of 3 stimulant medications or placebo. After 45-50 hours awake, participants were tested on computerized versions of the 5-Ring Tower of Hanoi (TOH), the Tower of London (TOL), and the Wisconsin Card Sorting Test (WCST). In-residence sleep-laboratory facility at the Walter Reed Army Institute of Research. Fifty-four healthy adults (29 men, 25 women), ranging in age from 18 to 36 years. Participants were randomly assigned to 1 of 3 stimulant medication groups, including caffeine, 600 mg (n=12), modafinil, 400 mg (n=12), dextroamphetamine, 20 mg (n=16), or placebo (n=14). At the doses tested, modafinil and dextroamphetamine groups completed the TOL task in significantly fewer moves than the placebo group, and the modafinil group demonstrated greater deliberation before making moves. In contrast, subjects receiving caffeine completed the TOH in fewer moves than all 3 of the other groups, although speed of completion was not influenced by the stimulants. Finally, the modafinil group outperformed all other groups on indices of perseverative responding and perseverative errors from the WCST. Although comparisons across tasks cannot be made due to the different times of administration, within-task comparisons suggest that, at the doses tested here, each stimulant may produce differential advantages depending on the cognitive demands of the task.